The Enthusiasm of Youth in Strengthening Character Through Creative Worship at Bukit Zaitun Church Makassar - Emanuel Omedetho Jermias; Abdul Rahman; Najamuddin Nasuhan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to elucidate the enthusiasm of the youth of GPIB Bukit Zaitun in participating in creative worship. This research uses qualitative research methods with a phenomenological approach. Data collection was conducted through participatory observation by directly engaging in the creative worship activities held at GPIB Bukit Zaitun. The results of these observations were then reinforced by conducting interviews with 2 pastors, 3 church council members, and 9 youths involved in the creative worship activities. The data that has been collected was then analyzed, interpreted, verified, and subsequently concluded. The research results show that the Bukit Zaitun church council provides support to the youth in creative worship activities. The goal is for GPIB Bukit Zaitun to be responsible for producing youth who are ready to carry out the Christian mission in supporting national development.There are eight factors that support the youth's enthusiasm in participating in creative worship, namely: the work of the Holy Spirit, service oriented towards gifts, prayer, praise and worship, music, engaging sermons, identity strengthening, and adequate church facilities. In addition, it is also supported by the factor of pastoral leadership that can motivate the youth